Numerical Simulation on Supercritical co2 Fluid Dynamics in a Hollow Fiber Membrane Contactor - Saavedra-Fenoglio, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
This research answers the following question: What is the fluid dynamic behavior of a supercritical fluid (SCF) inside a membrane module? At this time, there is very little or no reported information that can provide an answer to this question. The research studies related to the themes of supercritical CO2 (SC-CO2), hollow fiber membrane contactors (HFMCs), and numerical simulations have mainly reported on 2D simulations, but in this work, 3D profiles are presented. Simulations were performed based on the experimental results and other simulations, using the geometry of a commercial module. The results were mainly based on the different operating conditions and geometric dimensions. A mesh study was performed to ensure the mesh non-dependence of the results presented here. It was observed that the velocity profile developed at 10 mm from the wall of the supercritical CO2 entrance pipe. A profile equilibrium around the fiber close to the entrance of the module was achieved in the experimental hollow fiber membrane contactor when compared to the case of the commercial hollow fiber membrane contactor. The results of this research provided a visualization of the boundary layer, which did not cover the entire fiber length. Finally, the results of this paper are interesting for technical applications and contribute to our understanding of the hydrodynamics of SCFs. © 2019 by the authors.